Geometrie-Dreieck-Rechtwinkliges Dreieck


  • $A = \frac{a\cdot b}{ 2}$
    1 2 3 4 5 6 7 8 9 10 11 12
    $a = \frac{A \cdot 2}{ b}$
    1 2 3 4 5 6 7 8 9 10 11 12
    $b = \frac{A \cdot 2}{ a}$
    1 2 3 4 5 6 7 8 9 10 11 12
    $a^{2} + b^{2}=c^{2}$
    $c =\sqrt{a^{2} + b^{2} }$
    1 2 3 4 5 6 7 8 9 10 11 12
    $a =\sqrt{c^{2} - b^{2} }$
    1 2 3 4 5 6 7 8 9 10
    $b =\sqrt{c^{2} - a^{2} }$
    1 2 3 4 5
    $h^{2} = p\cdot q$
    $h = \sqrt{p\cdot q}$
    1 2 3 4
    $q = \frac{h^{2} }{p}$
    1 2 3 4
    $p = \frac{h^{2} }{q}$
    1 2 3
    $a^{2} = c\cdot p \qquad b^{2} = c\cdot q $
    $a = \sqrt{c\cdot p}$
    1 2 3
    $c = \frac{a^{2} }{p}$
    1 2 3 4
    $p = \frac{a^{2} }{c}$
    1 2 3 4

Beispiel Nr: 07
$ \text{Gegeben:}\\ \text{Kathete} \qquad a \qquad [m] \\ \text{Kathete} \qquad b \qquad [m] \\ \\ \text{Gesucht:} \\\text{Hypotenuse} \qquad c \qquad [m] \\ \\ c =\sqrt{a^{2} + b^{2} }\\ \textbf{Gegeben:} \\ a=\frac{1}{3}m \qquad b=\frac{3}{4}m \qquad \\ \\ \textbf{Rechnung:} \\ c =\sqrt{a^{2} + b^{2} } \\ a=\frac{1}{3}m\\ b=\frac{3}{4}m\\ c =\sqrt{(\frac{1}{3}m)^{2} + (\frac{3}{4}m)^{2} }\\\\c=0,821m \\\\\\ \small \begin{array}{|l|} \hline a=\\ \hline \frac{1}{3} m \\ \hline 3\frac{1}{3} dm \\ \hline 33\frac{1}{3} cm \\ \hline 333\frac{1}{3} mm \\ \hline 333333\frac{1}{3} \mu m \\ \hline \end{array} \small \begin{array}{|l|} \hline b=\\ \hline \frac{3}{4} m \\ \hline 7\frac{1}{2} dm \\ \hline 75 cm \\ \hline 750 mm \\ \hline 7,5\cdot 10^{5} \mu m \\ \hline \end{array} \small \begin{array}{|l|} \hline c=\\ \hline 0,821 m \\ \hline 8,21 dm \\ \hline 82,1 cm \\ \hline 821 mm \\ \hline 8,21\cdot 10^{5} \mu m \\ \hline \end{array}$